Comparison of Excess Weight Loss Outcomes Between Laparoscopic Sleeve Gastrectomy and Laparoscopic Mini Gastric Bypass in Morbidly Obese Patients (Iraqi Journal of Medical Sciences, 2023)
Background: Obesity is a complex, multifactorial, and largely preventable disease. The current most widely used criteria for classifying obesity is the body mass index (BMI). Surgical treatment for obesity (bariatric surgeries) has been shown to be effective for weight loss. The most performed bariatric surgeries were Roux-en-Y, nowadays; laparoscopic sleeve gastrectomy (LSG). laparoscopic mini gastric bypass (LMGB).Objective: To compare excess weight loss outcomes between LSG and LMGB. Methods: A prospective study; enrolling all patients underwent LSG and LMGB in Al-Imamein Al-Khadimein Medical City and number of private hospitals done by one surgical team during the period from January 1st to December 31st 2019. Patients initial BMI ranges from 45-55 kg/m2. All patients were given a dietary regime after the surgeries. Patients weight records were followed up to one year after their surgeries in 3-, 6-, 9- and 12-months' intervals.Results: Ninety-seven patients had been operated for LSG and LMGB; 50 of them met the inclusion criteria distributed as 25 patients operated for LSG and 25 patients operated for LMGB; 80% were females and 20% were males with mean age of 37.66±9.99 years. Both surgeries were successful in terms of excess body weight loss (EWL); mean EWL for LSG and LMGB (calculated as ideal BMI=24.9 kg/m2) at 3 months post-surgery follow up was 33.80±9.55% (P value 0.0001) with mean body weight 113.70±14.52 kg; 50.31±9.42 (P value 0.0001) at 6 months with mean body weight 102.36±12.83 kg; 62.06±9.75% (P value 0.0001) at 9 months with mean body weight 94.18±10.84 kg and 69.48±9.63 % (P value 0.0001) at 12 months follow up with mean body weight 88.90±9.61 kg. There was no significant difference for excess weight loss outcomes between LSG and LMGB in one year follow up. With Excess body weight loss at 12 months was 68.7% for LSG and 70.3% for LMGBConclusion: Both LSG and LMGB are effective for excess body weight loss with insignificant difference between their excess weight loss outcome in one-year post surgery follow up.Keywords: Obesity, laparoscopic sleeve gastrectomy, laparoscopic mini gastric bypass, excess body weight lossCitation: Nile AK, Joudah AI, Al-Zubaidi ASM. Comparison of excess weight loss outcomes between laparoscopic sleeve gastrectomy and laparoscopic mini gastric bypass in morbidly obese patients. Iraqi JMS. 2023; 21(2): 172-179. doi: 10.22578/IJMS.21.2.4
Keywords: Obesity; laparoscopic sleeve gastrectomy; laparoscopic mini gastric bypass; excess body weight loss